2015
DOI: 10.1016/j.mce.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ser-279/282 and Tyr-265 positions on Cx43 as possible mediators of VEGF-165 inhibition of pregnancy-adapted Ca2+ burst function in ovine uterine artery endothelial cells

Abstract: Normal pregnancy requires increased uterine endothelial cell driven vasodilation that is related to increases in sustained Ca2+ signaling via increased connexin 43 (Cx43) gap junction function. Preeclampsia, a hypertensive disorder of pregnancy associated with endothelial dysfunction, is also linked with down regulation of Ca2+ driven vasodilator production and increased levels of vascular endothelial growth factor (VEGF). Cx43 function can be acutely down-regulated by phosphorylation of multiple inhibitory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
4
21
1
Order By: Relevance
“…Moreover, it is known that GJ assembly and disassembly are events highly regulated by a sequence of protein kinase activation and phosphorylation events. This kind of regulation, as extensively reported for Cx43, has a net effect of reducing GJ communication [102][103][104]. Therefore, we may also postulate that VEGF-A or other factors released by PRP may reduce GJ/Cx43 functionality affecting such phosphorylation events.…”
Section: Factors Released By Prp Possibly Modulating CX Expression Ansupporting
confidence: 69%
“…Moreover, it is known that GJ assembly and disassembly are events highly regulated by a sequence of protein kinase activation and phosphorylation events. This kind of regulation, as extensively reported for Cx43, has a net effect of reducing GJ communication [102][103][104]. Therefore, we may also postulate that VEGF-A or other factors released by PRP may reduce GJ/Cx43 functionality affecting such phosphorylation events.…”
Section: Factors Released By Prp Possibly Modulating CX Expression Ansupporting
confidence: 69%
“…Common signaling ‘culprits’ that phosphorylate these inhibitory residues are Src, ERK, and PKC (Bird et al 2013). This has been corroborated in the ovine uterine artery endothelial cell model, where administration of VEGF leads to both phosphorylation of Cx43 and reduced sustained phase Ca 2+ signaling (Boeldt et al 2015). Inhibitors of Src and ERK signaling reversed phosphorylation of Cx43 at their respective target residues and also rescued Ca 2+ signaling to levels equivalent to control (Boeldt et al 2015).…”
Section: Effects Of Hormones Of Pe On the Endotheliummentioning
confidence: 75%
“…This has been corroborated in the ovine uterine artery endothelial cell model, where administration of VEGF leads to both phosphorylation of Cx43 and reduced sustained phase Ca 2+ signaling (Boeldt et al 2015). Inhibitors of Src and ERK signaling reversed phosphorylation of Cx43 at their respective target residues and also rescued Ca 2+ signaling to levels equivalent to control (Boeldt et al 2015). More detailed studies on other hormones (growth factors and cytokines) associated with of PE are warranted, to assess the universality of these initial observations, and whether they are indeed occurring in PE.…”
Section: Effects Of Hormones Of Pe On the Endotheliummentioning
confidence: 75%
“…These phosphorylations cause inhibition of intercellular communication which is well described for tumor cells (52). Previous reports have shown that cSrc phosphorylation suppresses gap junctional communication between endothelial cells (54), and the importance of Y265 has been suggested (8). Furthermore, paired cardiomyocytes from hamster in late-stage congestive heart failure have constitutively activated cSrc but Cx43 tyrosine phosphorylation was associated with suppressed intercellular communication (57).…”
mentioning
confidence: 90%